Investigation of the nutritional attitudes and behaviors of the adolescents of the age group of 16-18 who are engaged in sports and the ones who do not - Akil, Mustafa; Top, Elif; Yildiz, Serkan (Progress in Nutrition, 2019)
The present study was conducted to determine the nutrition exercise attitudes and nutrition exercise behaviors of adolescents the age group of 16-18 who actively perform sport activities and the ones who do not. The study was conducted on a study group comprised of 174 female (44.2%) and 220 male (55.8%) participants; totaling to 394 subjects. In terms of the gender distribution of the participating adolescents, while there is no significant difference between them based on the nutrition exercise behaviors scale, male adolescents displayed significant difference in the sub-factors of healthy nutrition, unhealthy nutrition and meal order in the nutrition exercise behaviors scale compared to the females (p